Safety and Pharmacokinetics of Multiple 750-Milligram Doses of Intravenous Levofloxacin in Healthy Volunteers - Chow, Andrew T. (American Society for Microbiology, 2001)
The safety and pharmacokinetics of a once-daily high intravenous dose of levofloxacin (750 mg) in 18 healthy volunteers were studied in a double-blind, randomized, placebo-controlled, single-center parallel group study. Levofloxacin was well tolerated, and higher maximum concentration of drug in serum and area under the concentration-time curve values were achieved. For difficult-to-treat infections, high daily doses of levofloxacin may be beneficial, and intravenous administration may be preferred in certain clinical settings, such as when treating patients in intensive care units, warranting further evaluation.